INCREASING STUDENTS’ VOCABULARY BY USING JUMBLED WORD FOR EIGHTH GRADE STUDENTS OF SMP NEGERI 3 BAMBEL ACADEMIC YEAR 2022/2023 - Priska Wahyuni; Septian Azwar; Putri Ayumi (STKIP USMAN SAFRI KUTACANE, 2025)
The objectives of the research were to describe process of increasing students’ vocabulary using Jumbled Words Media of SMPN 3 Bambel. The research methodology was classroom action research (CAR). The implementation of classroom action research was conducted in cycles 1. There were cycle I consisted of four meetings. This research involved eighth grade students which consisted of 23 students. The instrument of the research was data collecting technique, the data were tests (pre-test and post-tests), and questionnaire. The result of this research showed that there was a significant difference of the students’ achievement in pre-test and post-test. The average score of pre-test was 42.60%, while, after giving treatment in cycle I, the students average score in post-test I was 70%. It proved that mean score of both are very different. It means that Jumbled Word Media improves students’ vocabulary ability. Moreover, based on the analysis of the questionnaire, most of the students gave positive response (90%). Almost all students agreed that Jumbled Word strategy improves their ability in vocabulary and most of them said that Jumbled Word strategy were very helpful.